Rostral mandibulectomy for treatment of a sarcoma in a 16‐year‐old Thoroughbred mare. (8th February 2018) - Köhler, M.; Koene, M.; Schliewert, E.‐C.; Aupperle, H.; Krause, H.‐R.
Summary: A 16‐year‐old Thoroughbred mare presented with a 1‐year history of a growing mass on the rostral mandible. Biopsy performed by the referring veterinarian revealed chronic granulating fibrosis and stomatitis. Due to progressive loss of body condition and increasing size, the mare presented to the clinic. Radiographic examination of the mandible revealed osteolytic lesions. Mandibulectomy was performed under general anaesthesia. The horse's demeanour and feed intake improved significantly and the cosmetic outcome was acceptable. Histopathological examination confirmed a sarcoma, most likely a fibrosarcoma.